An exploration of interprofessional education between graduate entry medical and nursing students - Simpson, Christine (2019)
Interprofessional working practices are an important feature of contemporary healthcare. As the largest groups of workers within the healthcare arena, the working relationships between doctors and nurses are of prime importance to the delivery of quality care. Historically, tensions have existed between the two professions, and a key contributory factor is thought to stem from the sociological background to these professions. In order to break down these traditional barriers, an ethos of interprofessional working needs to be developed. One strategy to promote this is to integrate interprofessional education (IPE) into pre-registration curricula for medicine and nursing. Whilst the majority of pre-registration programmes for both medicine and nursing are at undergraduate level, some shortened graduate entry courses are available to students who have completed an undergraduate degree in another subject. Students who are enlisted on these courses are considered to have the knowledge, skills and attitudes associated with the notion of ‘graduateness’, which is acquired through completion of undergraduate study (Glover, Law & Youngman, 2002). As such, this unique group of students will bring specific qualities to interprofessional educational experiences. Although a body of evidence exists relating to IPE with undergraduate medical and nursing students, study focusing on the experiences of graduate entry students is lacking. This qualitative study was based in one UK university and focused on graduate entry medical and nursing students who were sharing an IPE initiative which was integrated into their programme of study. It explored the perceptions held by these students about each other and their experiences of IPE itself. The study consisted of two phases, Phase 1 commenced after introduction of the IPE experience with Phase 2 following its completion. Each phase included a survey, but the discussion of emerging themes is based upon findings from the life-grids completed in Phase 1 and the individual, semistructured interviews which were carried for both phases of the study. A total of seventeen interviews were carried out with graduate entry medical and nursing students. Four themes emerged from the data analysis; Previous Influences, Doctors- Individuals Within a Profession, Nurses -Individuals Within a Profession and Interprofessional Education. The individuality of members within medicine and nursing was recognised. Rather than assigning stereotypical images to the professions, graduate entry students develop their own perceptions of doctors and nurses. Despite the academic parity conferred by ‘graduateness’, nursing students needed to gain confidence when working with medical students. IPE was positively received as a component of the course, although suggestions were made for its improvement. An understanding of roles was developed during the IPE initiative. A key issue which emerged was the impact of public opinion on professional confidence. This study sheds light on the contribution of ‘graduateness’ to IPE shared by graduate entry medical and nursing students. It identifies implications for the design and implementation of IPE, which should include opportunities to explore the impact of contemporary issues on the confidence of professions.